Asymmetric synthesis of tetrahydroisoquinolines by enzymatic Pictet–Spengler reaction. Issue 4 (3rd April 2014) - Nishihachijo, Masakatsu; Hirai, Yoshinori; Kawano, Shigeru; Nishiyama, Akira; Minami, Hiromichi; Katayama, Takane; Yasohara, Yoshihiko; Sato, Fumihiko; Kumagai, Hidehiko
Abstract: Norcoclaurine synthase (NCS) catalyzes the stereoselective Pictet–Spengler reaction between dopamine and 4-hydroxyphenylacetaldehyde as the first step of benzylisoquinoline alkaloid synthesis in plants. Recent studies suggested that NCS shows relatively relaxed substrate specificity toward aldehydes, and thus, the enzyme can serve as a tool to synthesize unnatural, optically active tetrahydroisoquinolines. In this study, using an N -terminally truncated NCS from Coptis japonica expressed in Escherichia coli, we examined the aldehyde substrate specificity of the enzyme. Herein, we demonstrate the versatility of the enzyme by synthesizing 6, 7-dihydroxy-1-phenethyl-1, 2, 3, 4-tetrahydroisoquinoline and 6, 7-dihydroxy-1-propyl-1, 2, 3, 4-tetrahydroisoquinoline in molar yields of 86.0 and 99.6% and in enantiomer excess of 95.3 and 98.0%, respectively. The results revealed the enzyme is a promising catalyst that functions to stereoselectively produce various 1-substituted-1, 2, 3, 4-tetrahydroisoquinolines. Graphical abstract: : A practical 1-step synthesis of optically active 1-substituted tetrahydroisoquinolines by norcoclaurine synthase is described.